Divulgação científica na Amazônia: o laboratório de demonstrações da UFPA - CALDAS, Jocasta (Universidade Federal do Pará, 2018)
Science communication has a key role in democratizing the access to knowledge. In the last decades, many scientific diffusion initiatives emerged and developed in a process of expansion of institutions and investments. In the Brazilian Amazonia, the number of science communication actions is far less than what would be necessary to satisfactorily contemplate its vast territorial extension. The Demonstrations Laboratory of the Federal University of Pará, founded in 2004, has acted as a science center aiming the advancement of scientific literacy in the Brazilian Amazonia, as well as the dissemination and popularization of science and technology. We present the activities of this Demonstrations Laboratory over more than a decade of operation and the impact of its educational and science communication actions carried out in the Brazilian Amazonia.